AUNILO Pathfinder: An Initiative in Promoting ASEAN Rare Collections - Mohamad, Radia Banu Jan; Jan, Noor Azlinda Wan; Jaafar, Cik Ramlah Che; Misaridin, Shahriza Fadly; Yusof, Mahbob; Pattanakiatpong, Wararak (2015)
Librarians have been developing pathfinders as guide to resources for researchers to check and acquire various information resources needed to be used in learning, teaching and research. This paper would discuss the initiative taken by AUNILO (Libraries of ASEAN University Network) to create a pathfinder for rare collections and resources related to ASEAN which could be accessed online through AUNILO portal: http://aunilosec.org. AUNILO portal as a medium to share information about AUNILO and its activities will be the platform to promote and ensure the pathfinder listed could be accessed and benefitted by students and researchers inside and outside of ASEAN. The pathfinders linked in AUNILO portal are Kaum Peranakan Asia Tenggara (Peranakans), Lanna collection and .Mymanuskrip. Kaum Peranakan Asia Tenggara (Peranakans) consists of materials and documents related to the Peranakan people of Chinese, Jawi, Chetti and Sam-sam descendents developed by USM Library. Lanna collection consisting of materials about the Lanna people, their lifestyle and culture developed by Chiang Mai University Library while .Mymanuskrip developed by Universiti of Malaya has more than 179 titles of manuscripts in the archive. Pathfinders have enjoyed a particular niche and status in reference services and AUNILO is encouraging its members to showcase their online guides and to promote the ASEAN rare materials for research to the world.